RELATIONSHIP QUALITY IN ELECTRONIC COMMERCE - Moriguchi, Stella Naomi; Barbon Jr., Sylvio; Andrade, Darly Fernando; Murakami, Luiz Carlos (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
Technological innovation allows different strategies to attend wants and needs of customers. Compared to traditional physical stores, electronic commerce offers an easier access and search process to the buyer, allowing them to find the most suitable offer, concerning brands, price, delivery and freight. This landscape heightens the challenge for sellers to develop a relationship quality marketing with their clients instead of a transactional marketing approach, which sometimes means one sole purchase. This paper reports the construction of a model to measure the relationship quality between consumers and e-commerce sellers, exploring demographic variables, attitude, behavior and loyalty toward electronic purchase, perceived value, commitment, satisfaction and trust. A survey with a non-probabilistic sample from a Brazilian nationwide electronic commerce vendor database covered 2009-2013 period. The initial findings have led to expand the research to include perceived value, commitment, satisfaction and trust using Structural Equation Modeling.